Participação e caracterização da agricultura familiar na pedra do produtor da Ceasa-GO - Eugenio, Acássio Coêlho (2018)
A huge difficulty is to access marketing channels in the selling of family farming products. Even if their principle means of commercialization is known: institutional markets, fair markets and supply centers, information about family farming participation in National Supply Centers and producer’s markets is still incipient. The aim of this work is to characterize family farming who trades in the Producer’s Stone of Ceasa, Goias. This research is classified as exploratory using documental analysis and enriched with a case study, using a quali-quantitative approach in the analysis of the collected data. In order to characterize the productive profile of rural establishments for each producer who trades in the Stone, it was analyzed three years of a certificate of production emitted by Emater, Goias. For the characterization of each farmer and their respective socioeconomic profile, 138 farmers were interviewed. The collected data were grouped and tabulated in spreadsheets. Later, it was crossed and analyzed with the help of IBM SPSS statistics software. The results showed rural establishments with a 50-kilometer radius of Ceasa-GO, small areas of vegetable and fruit crops, and elevate crop diversification ; and with a massive use of agricultural technologies such as fertilization, liming and irrigation. 129 farmers of 138 (93,5%) were classified as family farming. Through this research, it was possible to map the principles rural establishments and family farmers of the agriculture greenbelt of Goiânia metropolitan region, responsable in supplying hortifruti products to Centre and North region of Brazil.